The Morphological Interference of Twitter Statuses of Javanese University Students - RAHMA, KHAIRUNNISA (LANTERN (Journal on English Language, Culture and Literature), 2016)
Twitter is one of the most popular social mediain Indonesia, for Indonesian people like to share their thoughts and opinions through this media. Since Indonesia is a multilingual country, we can find language interferencephenomenonin twitter statuses. The purpose of this study is to identify the language interference that took forms of morphological interferences on twitter. The study uses non-participant observation method to collect the dataand translational method to analyze the data. The findings of this research suggest that morphological interference of Javanese happens in the form of Javanese affixation. Factors that cause the interference to occur are the familiarity with more than one language, the environment and the prestige of using first language.